Risk Mitigation of Asymmetric Information in Mudharabah and Musyarakah Financing for SMEs: A Comparative Study of BSI and BMT in Salatiga - Eka Wahyu Priyo W; Aep Saepudin (INSANI: Jurnal Ilmu Agama dan Pendidikan, 2026)
This study aims to compare risk mitigation strategies for asymmetric information in Mudharabah and Musyarakah financing for MSMEs implemented by Bank Syariah Indonesia (BSI) Salatiga Branch and BMTs in Salatiga. This research employs a qualitative approach with a comparative case study design. Data were collected through in-depth interviews with financing officers and managers, analysis of financing procedure documents, and observation of customer monitoring practices. The findings show that BSI emphasizes structural mitigation through feasibility analysis, collateral substitutes, financial reporting, and digital monitoring systems. In contrast, BMTs rely more on cultural mitigation through personal approaches, social reputation, intensive mentoring, and spiritual values. The comparison indicates that structural mitigation is stronger in terms of procedural certainty and asset protection, while cultural mitigation is more adaptive to the informal characteristics of micro-enterprises. This study concludes that a hybrid model combining banking prudential standards and community-based supervision may strengthen profit-sharing financing for MSMEs.